PERANCANGAN APLIKASI GAJI KARYAWAN PADA PT. PP LONDON SUMATRA INDONESIA Tbk. GUNUNG MALAYU ESTATE - KABUPATEN ASAHAN - Adi Widarma; Hana Kumala (Universitas Asahan, 2017)
Abstrack - Salary is a wage given to employees who have worked in a particular company or agency. Every employee who works in a company has the right to get a salary in accordance with the rules or conditions in the company. The issue of giving a salary is important because it has a huge influence on the morale of its employees. At PT. PP London Sumatra Indonesia Tbk, Gunung Malayu Estate, the application used for processing employee payroll data is the Microsoft Office Excel 2010 application. Then an analysis of employee salary data processing systems at PT. PP. London Sumatra Indonesia Tbk by designing programming applications using NetBeans IDE 7.2.1 with the MySQl database. So that with the application of employee payroll data processing, it will improve the quality of service to its employees, because it will save time in data processing, and save time in payroll reports. Keywords - applications, salary systems, netbeans, mysql